2022
DOI: 10.3390/ijerph191710539
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on School-Aged Children’s Physical Activity, Screen Time, and Sleep in Hong Kong: A Cross-Sectional Repeated Measures Study

Abstract: Despite concerns about the negative effects of social distancing and prolonged school closures on children’s lifestyle and physical activity (PA) during the COVID-19 pandemic, robust evidence is lacking on the impact of the pandemic-related school closures and social distancing on children’s wellbeing and daily life. This study aimed to examine changes in the PA levels, sleep patterns, and screen time of school-aged children during the different phases of the COVID-19 outbreak in Hong Kong using a repeated cro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 53 publications
1
12
1
Order By: Relevance
“…Additionally, our study was conducted during COVID-19 pandemic and children's activities were limited. Their lifestyles changed dramatically ( 28 , 29 ), such as increased screen time ( 17 ) and decreased time outdoors ( 18 ), and their sleep would also be affected ( 19 ). People's lifestyle is also different from usual in a specific living environment, and children's myopic shifts are changed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, our study was conducted during COVID-19 pandemic and children's activities were limited. Their lifestyles changed dramatically ( 28 , 29 ), such as increased screen time ( 17 ) and decreased time outdoors ( 18 ), and their sleep would also be affected ( 19 ). People's lifestyle is also different from usual in a specific living environment, and children's myopic shifts are changed.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, due to the global pandemic of COVID-19, many countries have implemented social restrictions, including citywide lockdowns, home isolation, and school closures ( 16 ). These restrictions result in lifestyle changes dramatically, such as more screen time ( 17 ), less outdoor activities ( 18 ), and more sleep duration ( 19 ) among children. Compared with pre-COVID, the prevalence of myopia in children increased significantly ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent article in Hong Kong reported that that the average daily accumulation of moderate- or above-intensity physical activity time for primary and secondary school students was 15 min and 30 min, respectively, far short of the World Health Organization’s recommendation of 60 min [ 54 ]. Furthermore, time spent in front of electronic screens increased significantly due to the use of electronic products: primary school students’ screen usage increased from 2 h a day to 7 h a day before the pandemic, while middle school students’ screen usage increased from 8 to 9 h a day after the epidemic [ 54 ]. This might be due to the intermittent school closures since February 2020.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has been shown to affect children’s quality of life [4, 5, 6, 7, 8]. Further, restrictions related to the early phase of the pandemic were associated with more ST and less PA in children [4, 9, 10], as well with an adverse effect on mental health [11, 12].…”
Section: Introductionmentioning
confidence: 99%